Bottling fog? The quest for instructional management. Issue 4 (1st October 2016) - Murphy, Joseph; Neumerski, Christine M.; Goldring, Ellen; Grissom, Jason; Porter, Andy
Abstract : Elsewhere, the authors have unpacked instructional leadership and have documented that such leadership is associated with more effective schools. Indeed, there has been for a considerable time nearly universal acceptance that learning-centered leadership should provide the central platform on which leadership is enacted. In this paper, a less sanguine narrative is provided on instructional management. Specifically, it documents that for all the evidence and recognition of importance, learning-focused leadership remains a small domain of action for leaders at the school and district levels. It then focuses on both the culture of the profession of school administration and the nature of schooling to explain why in the face of considerable energy and effort only marginal improvements have been realized in deepening instructional leadership. It closes with an analysis of possible paths going forward.